Inflammatory Long Pentraxin 3 is Associated with Leukocyte Telomere Length in Night-Shift Workers - Pavanello, Sofia; Stendardo, Mariarita; Mastrangelo, Giuseppe; Bonci, Melissa; Bottazzi, Barbara; Campisi, Manuela; Nardini, Marco; Leone, Roberto; Mantovani, Alberto; Boschetto, Piera (Frontiers in Immunology, 2017)
Aging is an emerging worldwide threat to public health, even in the workplace, as it links with risk of illness and death. Bewildered inflammatory responses and stressful conditions associate with age-related disorders. Additionally, circadian rhythm disruption, a critical health issue in night-shift workers, correlates with premature aging. We investigated the hypothesis of a link between altered inflammatory response, detected by plasmatic long pentraxin 3 (PTX3), and biological aging, measured by leucocyte telomere length (LTL), attrition and possibly induced by night-shift work. Within the framework of a cross-sectional study, such possible relationships were appraised by simultaneous-equation-model (SEM) technique among day and night-shift hospital workers. PTX3 levels, modulated by several aging conditions [i.e., body mass index (BMI) (beta = -0.22; p=0.022), C-reactive protein (CRP) (beta = -0.07; p=0.000) and cardiovascular diseases with hypertension included (CVD) (beta = -0.12; p=0.000)], positively associate with LTL (coefficient = 0.15; p = 0.033). LTL, in turn is reduced by CVD (beta = -0.15; p=0.000), binge drinking (beta = -0.10; p=0.004), and CRP (beta = -0.05; p=0.026). On the other hand, night-shift work, found to be remarkably free from aging risk factors [i.e., age (beta = -0.13; p=0.017), BMI (beta = -0.17; p=0.030), CVD (beta = -0.14; p=0.000) and binge drinking (beta = -0.13; p=0.000)], does associate almost significantly with reversed PTX3 (coefficient = -0.09; p-value = 0.089) and even with CRP (beta = 0.17; p=0.000). In conclusion the SEM analysis indicates that PTX3 is positively linked to LTL. The finding suggests a possible new role of this long pentraxin that, by orchestrating an efficient governance of inflammatory processes, may protect telomere from attrition, ensuring therefore the genetic stability of cells. The higher CRP levels among night-shift workers suggest that night-shift work is associated with increased systemic inflammation. This would make nocturnal workers more susceptible to premature aging.